Effect of potassium fertilizer integrated with humic acid and cattle manure on tomato attributes and soil properties - Ibrahim, Muhammad; Khan, Qudrat Ullah; Khan, Muhammad Jamil; Ali, Iftikhar; Mamoon ur Rashid, Muhammad; Latif, Asif; Riaz, Muhammad; Saleem Ullah (Journal of Pure and Applied Agriculture, 2023)
: Potassium (K) integration with humic acid (HA) and cattle manure (CM) was investigated on tomato for growth, yield and quality along with their effect on soil physico-chemical characteristics. A pot culture experiment was designed including organic manures and K levels as two variable factors. Significantly higher number of fruits per plant and fruit weight were recorded in the plant parameters, while soil and quality parameters also showed significant effect of treatments. T